ChemInform Abstract: Cyclodextrin Host as a Supramolecular Catalyst in Nonpolar Solvents: Stereoselective Synthesis of (E)‐3‐Alkylideneoxindoles. Issue 13 (1st April 2014) - Asahara, Haruyasu; Kida, Toshiyuki; Hinoue, Tomoaki; Akashi, Mitsuru
Abstract The Knoevenagel reaction of oxindoles with cinnamaldehydes is accelerated with enhanced E/Z selectivities in the presence of 6‐O‐modified cyclodextrins as catalyst in nonpolar solvents.